A historical analysis of the criminal sanctions in the Malaysian copyright regime (1902–1969) - Adam, A. (Edward Elgar Publishing, 2016)
Criminal sanctions have long been accepted as an important component of domestic copyright systems. However, the beginnings of the application of criminal law to copyright infringements - which are essentially private wrongs - in national copyright regimes have been generally inadequately explored. This article seeks to shed light on the origins and reasons for introducing criminal sanctions in Malaysia by examining the early copyright acts, in particular, the Copyright Act 1930 (FMS) and the Copyright Act 1969 (Malaysia). In so doing, it: (1) examines the British Empire’s role in introducing copyright laws (and subsequently, criminal sanctions) in the states that make up modern Malaysia; and (2) analyses the legal transplantation process in Malaysia preand post-federation of Malaysia.